Effectiveness Of Psychoeducation And Assertive Training (PEAT) Combined For Improving Medication Adherence In Patients With Schizophrenia - Insiyah, Insiyah; Abdul Karim, Sairah; Othman, Zulhabri (JKG (JURNAL KEPERAWATAN GLOBAL), 2024)
Background: Non-adherence behaviors have a variety of causes, from suffering negative drug side effects to having scepticism regarding the effectiveness of recommended treatments. Recognising these complex relationships is essential to creating strategies that effectively manage the psychosocial as well as medical components of schizophrenia. The purpose of this study is to investigate how a combination of psychoeducation and assertive training can improve medication adherence in people with schizophrenia. Methods: A pretest-posttest quasi-experiment design was employed in this study as part of a quantitative research technique. Demographics and the Morisky Medication Adherence Questionnaire were used in conjunction with observation to collect data. Based on room-based simple random sampling, 80 patients with schizophrenia who met the inclusion criteria were split into two groups. Of these, 38 patients in the intervention group and 36 responders in the control group finished the study. This study made use of the five-stage Psychoeducation and Assertive Training (PEAT) module. Results: A combination of psychoeducation and assertiveness training (PEAT) was found to have an effect on medication adherence in this study. Following PEAT, patients with schizophrenia had a mean medication adherence of 5.92±1.29. The statistical test findings showed that the mean medication adherence of schizophrenic patients receiving PEAT differed significantly (p value <0x7E>0.001) from those who did not. Conclusion: Studies show that putting more of an emphasis on PEAT can help hospitals treat patients with schizophrenia more consistently by helping them take their medications as prescribed. Additionally, patients with schizophrenia should have a treatment plan that includes PEAT.